The Effect Of Cash Turnover, Receivable Turnover, And Inventory Turnover On Liquidity On Liquidity Of Consumer Goods Companies Listed In The Indonesia Stock Exchange In the 2011-2014 Period - Isna Asdiani Nasution; Friskilla Sembiring; Maisara Batubara; Tantri Octora Dwi Syah Putri (Enrichment : Journal of Management, 2022)
Consumer Goods Industry Company is one of the Manufacturing companies in Indonesia. it is still the main choice for investors to invest their funds. That's because the stocks of companies in the Consumer Goods Industry still offer the potential increase. The theory used in this research are theories that discuss the financial ratios turnover ratio of cash, accounts receivable turnover, inventory turnover, and liquidity. The method used in this research is the associative approach, the type of research is descriptive statistics, and the nature of this research is Explorative research. Data collection was performed by documentation, the type, and source of data are secondary data. Data analysis used multiple linear regression. The study population was the whole Consumer Goods Industry companies totaling 40 companies from 2011-to 2014. The samples were obtained from 17 companies that met the criteria for the research samples using the purposive sampling technique. The results showed that the partially, cash turnover does not affect liquidity, receivables turnover negatively affects the liquidity, and inventory turnover negatively affects liquidity. Simultaneously, cash turnover, receivable turnover, and inventory turnover significantly affect the liquidity in the Consumer Goods Industry companies listed on Indonesia Stock Exchange from the 2011-to 2014 period.